Inhibition of placental growth factor improves surgical outcome of glaucoma surgery. Issue 12 (9th October 2013) - Van, Tine; Jonckx, Bart; Hollanders, Karolien; Sijnave, Davine; Van de, Sarah; Vandewalle, Evelien; Moons, Lieve; Stassen, Jean‐Marie; Stalmans, Ingeborg
Abstract Excessive post‐operative wound healing with subsequent scarring frequently leads to surgical failure of glaucoma filtration surgery (trabeculectomy). We investigated the hypothesis that placental growth factor (PlGF) plays a role in post‐operative scar formation, and that it therefore may be a target for improvement of filtration surgery outcome. ELISA experiments showed that PlGF levels were significantly increased in aqueous humour of glaucoma patients and after VEGF treatment, which may indicate an important contribution of this growth factor to wound healing after trabeculectomy. Using a mouse model of glaucoma filtration surgery, we were able to show that intracameral injection of a previously characterized anti‐PlGF antibody (ThromboGenics NV) significantly improved surgical outcome by increasing bleb survival and bleb area. This was associated with a significant reduction in post‐operative proliferation, inflammation and angiogenesis during the first post‐operative days after surgery, and with a decrease in collagen deposition at later stages. Furthermore, inhibition of PlGF seemed to be more effective than anti‐VEGF‐R2 treatment in improving surgical outcome, possibly via its additional effect on inflammation. These results render PlGF an appealing target for ocular wound healing and point to potential therapeutic benefits of PlGF inhibition for the prevention of surgical failure.